Effect of Sector Vulnerability in the Rainfall, Wildlife Tourism Sector Performance Relationship in Maasai Mara Ecosystem, Kenya - Mose, Richard; Ngacho, Christopher; Odunga, Pius (Turizam, 2024)
Abstract This study sought to examine the role of sector vulnerability in the relationship between rainfall and wildlife tourism sector performance in Maasai Mara ecosystem, Kenya. This study is important because the Maasai Mara being a semi arid area is extremely vulnerable to the effects of climate change. The study adapted a pragmatic research approach that advocates for mixed methods research design. The study was based on a null hypothesis that sector vulnerability does not mediate the relationship between rainfall and wildlife tourism performance. Qualitative and quantitative data was collected using a questionnaire that was randomly administered to 466 respondents. Further qualitative data was collected by use interviews from 30 key informants purposively selected for the study. The results were analyzed using SPSS version 22 and AMOS version 21. The results showed that sector vulnerability mediated the relationship between rainfall and wildlife tourism performance β = - 0.439, t= -4.179, P<.001 this results were further collaborated by content analysis of qualitative data. The study concludes that wildlife tourism is extremely vulnerable to climate change indicator such as rainfall thus sector specific studies should be carried out so as to develop sector specific adaptations. Key words: Vulnerability, climate change, rainfall, wildlife tourism performace